Bacterial cellulose/lignin nanoparticles composite films with retarded biodegradability. (15th November 2021) - Tian, Dong; Guo, Yujie; Huang, Mei; Zhao, Li; Deng, Shihuai; Deng, Ouping; Zhou, Wei; Hu, Jinguang; Shen, Fei
Abstract: In practical applications, the full biodegradability of all-biomass-based bacterial cellulose (BC) composites enhances their environmentally friendliness but results in the poor durability especially at humid conditions. This work prepared BC/lignin nanoparticles (LNPs) composite films with retarded biodegradability, which could broaden their application area. Three LNPs were fabricated using technical lignins extracted by deep eutectic solvent (DES), ethanol organosolv, soda/anthraquinone from poplar. LNPs involvement during BC fermentation showed limited influence on its productivity but significantly retarded the biodegradation of composite films. The potential inhibition mechanism was physical barrier and non-productive binding of LNPs. The BC/Soda LNPs showed much higher retarded degradation property ( 58 wt% degradation) compared to BC/Organosolv LNPs and BC/DES LNPs ( 85 wt% and 97 wt% degradation respectively) at high enzyme loadings of 5 mg g −1 BCE. While at low enzyme loadings of 1 mg g −1 BCE, all these three composite films showed comparable retarded degradation property of 60 wt%. Graphical abstract: Unlabelled Image